Analisis Yuridis PHK Karyawan CNN Indonesia: Tinjauan Kebebasan Berserikat dan Dugaan Praktik Union Busting - Nur Prasetyo, Andika; Argya Azzahrani, Salma; Tri Hapsari, Feti (PT. Meja Ilmiah Publikasi, 2026)
Research examines the issue of unionization and procedure for layoffs in the context of employment in Indonesia with a normative-empris approach. The normative approach was carried out with relevant legal regulations, especially Law No. 13 of 2003 concerning labor and Law No. 21 of 2000 concerning serikat work. The empirical approach was carried out with the analysis of the regulatory implementation terhadp, a real case of layoffs to CNN workers Indonesia, By conducting a review of the field facts, the chronology of the events and the relevant parties. The results of the analysis revealed that the large number of industries in Indonesia need to be balanced with strong and protective labor policies, the government's steps not only focus on creating new jobs but also on preventing layoffs through social pungguatan dialaog. The increase in labor competence and the establishment of healthy industrial relations climate, CNN Indonesia's Case shows the urgency of a more responsive and relevant industrial relations system for workers’ basic rights protection. The findings of this study concluded that the gap between regulations and field practice is still a big problem in the employment world in Idonesia, struktual Reform is needed to minimize the practice of labor unions and realize fair, sustainable and in accordance with the principles of modern labor law.